A study on contribution of service quality, price, corporate image and customers' satisfaction towards customer loyalty case study of Telekom Malaysia Kota Bharu region / Hasbullah Zakaria - Zakaria, Hasbullah (Faculty of Business and Management, 2008)
The rapid changing and development in world business, forced organization that are in the telecommunication industry to look for something new and different if they want to be the best. They have to be different in their marketing activities and concern more about the social and current issues. The title of this study is “A study on contribution of Service Quality, Price, Corporate Image and Customers’ Satisfaction towards Loyalty of TM’ customers (Kota Bharu Region)”. Since equal access is being allowed, TM especially in Kota Bharu are facing few problems in maintaining its customer loyalty and at the same time to attract the new customers towards its telephony services. Base on observations and interview, the researcher was chose four independents variable such as service quality, price, corporate image and customer satisfaction. The data are collected through questionnaires that are distributed to the customers of Telekom Malaysia Kota Bharu Region (TMKBR). The population of customers at TMKBR is 90,000 but only 200 sample sizes are used, because of few constraints such as time and money. The result of the research revealed that most of the respondents are really happy with the services provided by TMKBR. Most of the variables measured in this study received a neutral rating. In other hand TM should upgrade its services from good to excellence in order to maintain the existing customers and tackle a new customers. It is also to prevent from switching to the competitors. As a recommendation, the company should improve the performance and maintain its customers loyalty towards the services provided. At the same time hopefully the company will able to retain and gain more customers. At the end of the paper, few recommendations are made in order for the company to improve its performance and maintain its customer loyalty towards the services provided.